Intuition, Analysis and Reflection in Business Ethics - Provis, Chris (Journal of business ethics, 2017)
The paper aim draws together two ideas that have figured in different strands of discussion in business ethics: the ideas of intuition and of reflection. They are considered in company with the third, complementary, idea of analysis. It is argued that the interplay amongst these is very important in business ethics. The relationship amongst the three ideas can be understood by reference to parts of modern cognitive psychology, including dual-process theory and the Social Intuitionist Model. Intuition can be misleading when based on fast and frugal heuristics, and reasoning needs social exchange if it is to support moral judgment effectively, but in the complex institutional environment of business, reflection and analysis can underpin social communication and feedback to develop sound intuition. Reflection and analysis are both more deliberate, systematic judgment processes than intuition, but are distinguished by the fact that reflection embraces hypothetical thinking and imagination, while analysis is careful, step-by-step reasoning. Examples of business ethics problems illustrate the need for both of these processes, and also suggest how they themselves can be enhanced in the same social exchange process that underpins the development of good intuition.